Pengendalian Persediaan Bahan Baku Dengan Metode Economic Order Quantity (Eoq) Pada Cv. Suka Bersama - Sari, Hesti Indah; Siregar, Ninny; Silviana, Nukhe Andri (Universitas Medan Area, 2022)
CV. Suka Bersama is an MSME (Micro, Small Medium Enterprises) in plastic straws (pipettes) manufacture. The main materials used in the process of making this pipette are polypropylene and dye which consists of three colors, namely yellow, green, and red. Currently CV. Suka Bersama only used estimates in raw materials purchasing. If the raw materials ran low in the warehouse, then CV. Suka Bersama had to reorder raw materials based on use, so it often had the unavailability and excess stocks in the warehouse. Where there was excess, there would be additional costs, and if there was less, production would be hampered. One way that could be used to overcome this was by applying ordering raw materials using the Economic Order Quantity (EOQ) method which was used to determine the number of orders or purchases that might be made and how many quantities might be ordered. So that the total costs in the sum of ordering and storage costs were a minimum, raw material inventory control and how to apply the economic order method, safety stock reorder point, and total cost in controlling raw material inventory. By calculating the raw material inventory issued by the company was Rp. 4,429,969 while using the EOQ method was Rp. 979,110 of the total cost of raw material inventory was more efficient using the EOQ method with a difference of Rp. 3,450,859.